WORD OF MOUTH MARKETING STRATEGY AND ITS IMPACT ON PURCHASING DECISIONS - Feliks Anggia Binsar Kristian Panjaitan (Adisam Publisher, 2025)
This research aims to systematically examine Word of Mouth Marketing (WOMM) strategies and their impact on consumer purchasing decisions. Using a qualitative descriptive approach, this study analyzes various relevant academic literature in the 2015–2025 time period, including indexed journals and scientific books. The study results show that WOMM is an effective strategy in influencing purchasing decisions, especially through three main impact channels: cognitive (consumer knowledge), affective (attitudes and perceptions), and conative (purchasing intentions and actions). Commonly used strategies include share-worthy content, consumer reviews, online communities, and utilizing social media. The effectiveness of WOMM is influenced by industry factors, demographic characteristics, and the level of consumer involvement in the product or service. These findings have theoretical implications in the development of consumer behavior studies and practical implications for business people in designing marketing strategies that are more authentic and based on consumer experience. WOMM has proven to be not just a promotional tool, but a direct reflection of the quality of the relationship between a brand and its customers.